2016
DOI: 10.1161/jaha.115.003120
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Recommended Medical Therapy for Cardiovascular Diseases in the Obese: Insights From the Veterans Affairs Clinical Assessment, Reporting, and Tracking (CART) Program

Abstract: BackgroundStigma against the obese is well described in health care and may contribute to disparities in medical decision‐making. It is unknown whether similar disparity exists for obese patients in cardiovascular care. We evaluated the association between body mass index (BMI) and prescription of guideline‐recommended medications in patients undergoing elective percutaneous coronary intervention.Methods and ResultsUsing data from the Veterans Affairs Clinical Assessment, Reporting, and Tracking System Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Dr. Flegal thinks that the "obesity paradox" terminology is essentially a rhetorical device in which the researchers collect a range of current studies together and further identify a unitary phenomenon showing an unexpected benefit of clinically diagnosed obesity (BMI ≥30 kg/m 2 ). Such findings can be easily influenced by a variety of confounding factors that may differ across diseases and treatments, and are not necessarily mutually exclusive, such as the selection bias from the retrospective nature (11), undetected cachexia (12), weight loss induced by chronic wasting diseases before surgery (13), and lower likelihood of receiving guidelinerecommended treatments (14). The "obesity paradox" terminology oversimplifies a complex of underlying pathophysiological mechanisms.…”
mentioning
confidence: 99%
“…Dr. Flegal thinks that the "obesity paradox" terminology is essentially a rhetorical device in which the researchers collect a range of current studies together and further identify a unitary phenomenon showing an unexpected benefit of clinically diagnosed obesity (BMI ≥30 kg/m 2 ). Such findings can be easily influenced by a variety of confounding factors that may differ across diseases and treatments, and are not necessarily mutually exclusive, such as the selection bias from the retrospective nature (11), undetected cachexia (12), weight loss induced by chronic wasting diseases before surgery (13), and lower likelihood of receiving guidelinerecommended treatments (14). The "obesity paradox" terminology oversimplifies a complex of underlying pathophysiological mechanisms.…”
mentioning
confidence: 99%
“…Such results may be due to multiple factors that may differ by disease and by treatment and that are not necessarily mutually exclusive. It has been suggested that the apparent survival benefit among patients with overweight and obesity is explained by worse health among patients with normal weight, perhaps because of selection bias , undetected cachexia , weight loss due to illness , or lower likelihood of receiving guideline‐recommended treatments . Perhaps instead of the “obesity paradox,” we should be studying the “normal weight paradox” to find why normal weight isn't associated with better survival.…”
mentioning
confidence: 99%
“…Estimates vary, but between 20% and 40% of Veterans have a psychiatric diagnosis and nearly 80% are living with overweight or obesity . Furthermore, Veterans are at a significantly higher risk of developing CVD than non‐Veterans, and over half of Veterans undergoing PCI have obesity . The Veterans Affairs (VA) Clinical Assessment Reporting and Tracking (CART) program currently collects clinical and procedural data on Veterans undergoing coronary angiography and PCI across VA cardiac catheterization laboratories.…”
Section: Introductionmentioning
confidence: 99%